Is a "firm" a firm? A Stackelberg experiment - Andreas Hildenbrand (Kiel Institute for the World Economy (IfW), 2012)
Industrial organization is mainly concerned with the behavior of large firms, especially when it comes to oligopoly theory. Experimental industrial organization therefore faces a problem: How can firms be brought into the laboratory? The main approach relies on framing: Call individuals firms! This experimental approach is not in line with modern industrial organization, according to which a firm's market behavior is also determined by its organizational structure. In this paper, a Stackelberg experiment is considered in order to answer the question whether framing individual decision making as organizational decision making or implementing an organizational structure is more effective in generating profit-maximizing behavior. Firms are either represented by individuals or by teams. Teams are organized according to Alchian and Demsetz's (1972) contractual view of the firm. I find that teams' quantity choices are more in line with the assumption of profit maximization than individuals' choices. Compared to individuals, teams appear to be less inequality averse.
Keywords: C72; C91; C92; D43; L13; 330; industrial organization; Stackelberg game; individual behaviour; team behaviour; framing; experimental economics